TINJAUAN IZIN PENGUSAHAAN SUMBER DAYA AIR KEMENTERIAN PUPR KEPADA PDAM KOTA MALANG. - Jasmine Sabina Marsheryne; Sri Untari Indah Artati (Fakultas Hukum Universitas Trisakti, 2022)
Every use of water must have a permit, as stated in Article 44, Paragraph 1, of Law No. 17 of 2019 Concerning Water Resources (SDA). The process for obtaining a permit to use natural resources is also outlined in the Minister of PUPR's Regulation No. 01/PRT/M/2016. What are the legal repercussions of the Ministry of PUPR issuing water resources exploitation permits to PDAM Malang City, and is the granting of water resources exploitation permits to PDAM Malang City issued by the PUPR Ministry in accordance with applicable regulations? Research is being done using a normative legal approach. descriptive research's structure, data collection methods, and literature analysis. digesting data, analyzing it qualitatively, and making deductions. The study's findings, analysis, and conclusion are as follows: issuing permits for the exploitation of natural resources to PDAM Malang is not appropriate due to their disregard for the procedures outlined in Law No. 32 of 2009 UUPPLH, Law No. 11 of 2020 concerning Job Creation, and Minister of PUPR Regulation Article 24 paragraph (1) letter l, as well as the potential legal repercussions of issuing these permits in the form of a conflict over the management of natural resources.